Identification of research priorities in infertility and assisted reproduction: an international, multicentre study. Issue 2 (February 2020) - García, Désirée; Brazal, Sarai; Lindenberg, Frederikke; Toft, Eva; La Marca, Antonio; Borrás, Rosa; Lorenzon, Aline Rodrigues; Chehin, Mauricio Barbour; Silva, Leticia; da Motta, Eduardo Leme Alves; Ripero, Maider; Madero, José Ignacio; et al.
Abstract: Research question: What are the main research interests among patients of assisted reproductive technologies (ART)? Design: Cross-sectional study consisting of an anonymous online survey sent to 2112 patients from eight centres in four countries in 2018. Patients were asked to identify research questions relevant to them in the field of infertility and ART. Answers were categorized into topics and ranked by frequency. A long list of the top 30 research topics was extracted from the aggregate results, from which a short list of the top 10 research topics was created. Ten research questions were finally formulated. Results: A total of 945 responses were analysed. Main interests were side-effects, success rates, infertility prevention and emotional support. The 10 research questions were: 1. What are the side-effects of drugs used in ART treatments? (51.6%). 2. What are the most effective methods to cope with infertility from the psychological point of view? (35.7%). 3. What effects could diet have on fertility? (25.9%). 4. What are ART success rates per clinical profile? (24.8%). 5. Are there some habits and lifestyle factors that could prevent infertility? (20.0%). 6. What are the long-term risks associated with ART in mother and child? (18.5%). 7. Are alternative therapies such as acupuncture, yoga and meditation effective to treat/prevent infertility? (18.5%). 8. What is the impact of exercise on fertility? (15.4%). 9. How does oocyte quantity and quality affect fertility? (9.5%). 10. What are the genetic patterns or hereditary conditions causing/related to infertility? (9.5%). Conclusions: Researchers and clinicians should keep in mind that, in addition to success rates and safety, patients greatly value research into causes, prevention and emotional aspects of infertility.